Analisis TAM terhadap Faktor-Faktor yang Mempengaruhi Penerimaan Mahasiswa Baru untuk Aplikasi Ruangguru - Ronald Antonius Panjaitan (STIKes Ibnu Sina Ajibarang, 2024)
The emergence of a new paradigm in the field of education and increasingly advanced technological developments, namely the emergence of an electronic learning system known as E-learning. One of the most popular E-learning media in Indonesia is the Ruangguru online learning application which can be accessed via Smartphone. The purpose of this study was to analyze the factors that influence student acceptance of the Ruangguru application using the Technology Acceptance Model (TAM) method. 5 (five) TAM research model constructs were used, namely Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using Behavioral Intention of Use and Actual System Use. Data collection used was an online questionnaire from Google Form with a purposive sampling technique. Valid questionnaire data was processed using the SmartPLS 3 program with 3 (three) structural analysis models, namely Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing.